Componentes estruturais abiótico e biótico e caracterização do grau de trofia de gamboas do litoral sul do Paraná, Brasil - Siqueira, Adriana (Universidade Federal de São Carlos, 2006)
Studies related to the quality of the water in coastal environments as bays, estuaries and tidal creeks are important due to the high productivity and intense influence of anthropic activities in these areas. This study aims the physical, chemical and microbiological characterization of diverse tidal creeks along Paraná coast. We analized seasonal variations in four tidal creeks and differences among rainy and dry periods in two tidal creeks. The cellular density of the pico, nano and microplanktonic fractions in different trophic conditions, differentiating the auto and heterotrofic compartments were performed. The temperature, salinity, pH, alkalinity, CO2, dissolved oxygen, nitrite, nitrate, ammonium, phosphate, silicate, suspended matter, particulate organic and humic matter, total chlorophyll, total coliforms and Escherichia coli were analyzed. The pico- and the nanoplankton were analyzed by direct counting under epifluorescence microscopy, while the microphytoplankton and the protozooplankton were through the Utermöhl method. In relation to the physico-chemical and biological characteristics the Perequê tidal creek exhibited larger saline intrusion, and in the Olho d´Água tidal creek was detected great amount of discharged domestic effluents. Among the pico- and nanoplanktonic fractions prevailed the heterotrophic compartment, in both phases. On the other hand, the abundance of the phytoplankton prevailed under the protozooplankton in the microplanktonic fraction along the whole study. Differences between dry and rainy periods were confirmed. In the rainy period was observed in the two tidal creeks an increase in nitrite, suspended matter, organic particulate matter and picoplankton and a reduction of nitrate, chlorophyll, nanoplankton (auto- and heterotrophic) and of the autotrophic microplankton. Increase of phosphate, ammonium and humic substances were only observed in Barranco tidal creek and of dissolved oxygen and E. coli in Olho d´Água. These results show that in periods of high pluviosity elevated amounts of nutrients are exported by the tidal creeks to the adjacent internal continental shelf. It was not possible to define a pattern for none of the variables in relation to the tide and to the day and night periods.
Keywords: Ecologia microbiana; Fitoplâncto; Maré; Picoplâncton; Nanoplâncton; Protozooplâncton; Estado trófico; Tidal creek; Picoplankton; Nanoplankton; Phytoplankton; Protozooplankton; Tide; Trophic state; CIENCIAS BIOLOGICAS::ECOLOGIA